Plant communities and habitat types in the protected area of Lake Pamvotis (Epirus, Northwestern Greece) - Sarika, Maria; Christopoulou, Anastasia; Zikos, Andreas; Kazanis, Dimitrios; Bazos, Ioannis (Mediterranean Botany, 2020)
The vegetation of the protected area of Lake Pamvotis (Epirus, NW Greece) was studied and classified into habitat types according to the Council Directive 92/43/EEC. The main vegetation types encountered in the Ioannina Basin and the south-western part of Mt Mitsikeli are: (1) Quercus coccifera shrublands, (2) degraded deciduous oak forests, (3) Mediterranean arborescent mattorals with Juniperus, (4) Oro-Mediterranean heathlands, (5) willow low open forests, (6) οriental plane woods, (7) plant communities supported by calcareous substrates, (8) aquatic macrophyte assemblages, (9) reed beds and rush meadows. Twenty plant communities belonging to twelve alliances, eleven orders, and ten phytosociological classes were discerned. The Asplenio ceterach-Aurinietum saxatilae is described as a new association and the Eleocharito palustris-Alismatetum lanceolati is reported for the first time from Greece. Eleven habitat types were identified and their conservation status was assessed. Three habitat types (4090, 8210, 91M0) were in favourable conservation status, while one (5210) is in unfavourable-bad conservation status. The rest are in unfavourable-inadequate conservation status, with several pressures and threats recorded.